2020
DOI: 10.3390/ijms21031133
|View full text |Cite
|
Sign up to set email alerts
|

Arginase Inhibition Supports Survival and Differentiation of Neuronal Precursors in Adult Alzheimer’s Disease Mice

Abstract: Adult neurogenesis is a complex physiological process, which plays a central role in maintaining cognitive functions, and consists of progenitor cell proliferation, newborn cell migration, and cell maturation. Adult neurogenesis is susceptible to alterations under various physiological and pathological conditions. A substantial decay of neurogenesis has been documented in Alzheimer’s disease (AD) patients and animal AD models; however, several treatment strategies can halt any further decline and even induce n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…In this context, recent findings demonstrated that the treatment of 3×Tg mice with the arginase inhibitor L‐norvaline induced a cognitive improvement associated with a reduction in neuroinflammation and levels of β‐amyloidosis. In addition, this treatment was able to reverse the reduction of dendritic spine density in the hippocampus [85,86].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, recent findings demonstrated that the treatment of 3×Tg mice with the arginase inhibitor L‐norvaline induced a cognitive improvement associated with a reduction in neuroinflammation and levels of β‐amyloidosis. In addition, this treatment was able to reverse the reduction of dendritic spine density in the hippocampus [85,86].…”
Section: Discussionmentioning
confidence: 99%
“…The spatial memory was significantly improved in the treated animals, and the improvement was associated with a reduction in neuroinflammation. Additionally, we evidenced a treatment-related decline in β-amyloidosis [ 167 ], followed by an improvement in the BBB integrity [ 168 ] and neurogenesis [ 169 ]. Of note, the hippocampal levels of Arg1 protein significantly reduced following the treatment.…”
Section: Polyamine Pathway In Alzheimer’s Diseasementioning
confidence: 99%
“…Our data proved that HDAC4 levels decrease dramatically following the treatment with norvaline. Moreover, its functionally active form, demonstrated a substantial reduction in levels [ 169 ]. Of importance, HDAC inhibitors are promising AD-modifying agents [ 171 ], therefore, we speculate that HDAC is partially responsible for the phenotype we observed.…”
Section: Polyamine Pathway In Alzheimer’s Diseasementioning
confidence: 99%
“…ROS have been shown to instigate Arg1 expression levels and activity [58]. Arg2 levels also escalate signi cantly as a reaction to hypoxia, as well as bacterial lipopolysaccharides, tumor necrosis factoralpha (TNFα), and oxidized low-density lipoproteins [59]. Remarkably, Arg2 activation in mammals is associated with its translocation from the mitochondria to the cytosol [55,60].…”
Section: Discussionmentioning
confidence: 99%